2020
DOI: 10.1016/j.appet.2020.104719
|View full text |Cite
|
Sign up to set email alerts
|

Anticipation of 24 h severe energy restriction increases energy intake and reduces physical activity energy expenditure in the prior 24 h, in healthy males

Abstract: Intermittent fasting involves alternating between severely restricted and unrestricted energy intake. Physical activity energy expenditure (PAEE) is reduced during, and energy intake is elevated after, a period of energy restriction, but whether these are altered in anticipation of energy restriction is unknown. The aim of this study was to assess energy intake and PAEE in the 24 h before severe energy restriction. In randomised, counterbalanced order, 14 healthy males completed two 48 h trials over 3 days. On… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 40 publications
2
11
0
Order By: Relevance
“…The reduction in light PA on fast days observed in the current study is in line with extended morning fasting (breakfast-skipping) studies, which found that PA was lower (especially in the morning), with extended morning fasting in both lean individuals and individuals with obesity [7,8]. Moreover, a recent acute cross-over study in lean males found reduced AEE on both the preceding feed day and on the fast day (25% energy requirements) [11]. Importantly, the current study extends on previous IER intervention studies (e.g.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The reduction in light PA on fast days observed in the current study is in line with extended morning fasting (breakfast-skipping) studies, which found that PA was lower (especially in the morning), with extended morning fasting in both lean individuals and individuals with obesity [7,8]. Moreover, a recent acute cross-over study in lean males found reduced AEE on both the preceding feed day and on the fast day (25% energy requirements) [11]. Importantly, the current study extends on previous IER intervention studies (e.g.…”
Section: Discussionsupporting
confidence: 91%
“…Acute cross-over severe energy restriction studies have shown increases in hunger on an energy restricted day compared to an energy balance day, e.g. James et al with 75% energy restriction [11]. However, intervention studies have shown that fast-day hunger does not change [3] or decreases [2] Food cravings generally improved (craving control and craving for savoury foods) or did not change (craving for sweet foods) during IER, with no fast-feed day differences.…”
Section: Discussionmentioning
confidence: 99%
“…Of note is a relative large recent study ( n = 116 adult participants) that reported reductions in appendicular FFM by dual-energy X-ray absorptiometry with TRE over 12 weeks ( 87 ), which may be more representative of skeletal muscle mass than total FFM ( 88 ). Many of the studies mentioned above prescribe variations of IF as the independent variable but do not explicitly control dietary intake ( 19 , 69 , 70 , 72 78 , 81 , 89 , 90 ) and/or physical activity ( 19 , 69 72 , 75 78 , 80 , 89 , 90 ), the latter of which is important to consider given that spontaneous physical activity may be modified by restricted eating ( 91 ) and can also influence the sensitivity of skeletal muscle to dietary AA ( 92 ). When IF is coupled with the potent anabolic stimulus of resistance exercise, a systematic review ( 93 ) observed no significant differences in FFM outcomes when compared to those resistance training with a normal diet.…”
Section: Discussionmentioning
confidence: 99%
“…This may result from an anticipatory compensatory behavior. This phenomenon can be cognitive, for example when a high-EE exercise (Barutcu, Taylor, Mcleod, Witcomb, & James, 2020) or a 24-hr severe energy restriction (James, James, & Clayton, 2020) is planned, leading subjects to increase intake at the prior meal or in the prior 24 hr, respectively, or conditioned, such as in humans omitting their habitual afternoon meal during 1 month, with a progressive increased EI at lunch (Chapelot et al, 2006). Even if we have no direct evidence in support of this hypothesis, this is consistent with the well-known superior adaptive power of anticipatory behaviors in energy homeostasis .…”
Section: Discussionmentioning
confidence: 99%